2015
DOI: 10.3390/en81010558
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Forestland Dynamics in a Typical Deforestation and Afforestation Area under Climate Scenarios

Abstract: Forestland dynamics can affect the ecological security of a country and even the global environment, and therefore it is of great practical significance to understand the characteristics of temporal and spatial variations of forestland. Taking Jiangxi Province as the study area, this study first explored the driving mechanism of the natural environment and social economy on deforestation and afforestation using a simultaneous equation model. The results indicate that population size, topographic and geomorphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…By analyzing, interpreting and validating, FAO in consultation with SUPARCO and Crop Reporting Services of Punjab have identified 13 main land use classes in the high resolution spatial satellite data of SPOT-5 at a scale of 1:25,000 [59]. For meeting the requirement of DLS, we prepared all land use and driving data in uniform spatial resolution and projection of 1 km × 1 km [29,60]. Subsequently, 13 land use types were reclassified into six classes [28,31,32,35] with coding 0 to 5 (Table 1) and generalized via a separate spatial representation scheme [28].For the study analysis, we adopted the land use data from 2010 to evaluate the accuracy of simulation results from the DLS model.…”
Section: Land Use Datamentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing, interpreting and validating, FAO in consultation with SUPARCO and Crop Reporting Services of Punjab have identified 13 main land use classes in the high resolution spatial satellite data of SPOT-5 at a scale of 1:25,000 [59]. For meeting the requirement of DLS, we prepared all land use and driving data in uniform spatial resolution and projection of 1 km × 1 km [29,60]. Subsequently, 13 land use types were reclassified into six classes [28,31,32,35] with coding 0 to 5 (Table 1) and generalized via a separate spatial representation scheme [28].For the study analysis, we adopted the land use data from 2010 to evaluate the accuracy of simulation results from the DLS model.…”
Section: Land Use Datamentioning
confidence: 99%
“…Natural forest includes closed forest with canopy cover more than 60% and open forest with canopy cover [59]. For meeting the requirement of DLS, we prepared all land use and driving data in uniform spatial resolution and projection of 1 km × 1 km [29,60]. Subsequently, 13 land use types were reclassified into six classes [28,31,32,35] with coding 0 to 5 (Table 1) and generalized via a separate spatial representation scheme [28].…”
Section: Forestry Areamentioning
confidence: 99%
“…The DLS model is a widely practiced model of simulation of the land system [32,[37][38][39][40][41]. DLS model has two special features: firstly, it provides scenario analysis of land demand at regional level and spatial integration of land uses at pixel level.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the north-south vegetation trend of the Yangtze River Delta before or after abrupt change was closely related to the land use type. Some studies have suggested that the increase in the vegetation of woodland in the south of the Yangtze River Delta was related to human-related policies such as ecological protection projects [61]. The urbanization in the eastern cities and the irrational human use of cropland [62][63][64] had led to a great increase in vegetation browning of cropland and built-up land.…”
Section: Effects Of Land Use Changes On Relationship Between Annual Mmentioning
confidence: 99%